2019
DOI: 10.3389/fpsyt.2019.00034
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Gut Microbiota and Major Depression

Abstract: Background: Recently discovered relationships between the gastrointestinal microbiome and the brain have implications for psychiatric disorders, including major depressive disorder (MDD). Bacterial transplantation from MDD patients to rodents produces depression-like behaviors. In humans, case-control studies have examined the gut microbiome in healthy and affected individuals. We systematically reviewed existing studies comparing gut microbial composition in MDD and healthy volunteers.Methods: A PubMed litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
296
3
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 438 publications
(357 citation statements)
references
References 151 publications
21
296
3
7
Order By: Relevance
“…Recent study has established noteworthy changes in profusion levels among phyla and genera in the gut microbial community; in the meantime, the metabolism of tryptophan and bile acids was also disturbed after chronic variable stress intervention . Recently, Stephanie Cheung et al reported that the largest number of differentiating taxa was within phylum Firmicutes; nine genera were higher in major depressive disorder . Jessica M et al have reported that indigenous spore‐forming bacteria control metabolites that stimulate colon 5‐HT biosynthesis from colonic enterochromaffin cells .…”
Section: Discussionmentioning
confidence: 99%
“…Recent study has established noteworthy changes in profusion levels among phyla and genera in the gut microbial community; in the meantime, the metabolism of tryptophan and bile acids was also disturbed after chronic variable stress intervention . Recently, Stephanie Cheung et al reported that the largest number of differentiating taxa was within phylum Firmicutes; nine genera were higher in major depressive disorder . Jessica M et al have reported that indigenous spore‐forming bacteria control metabolites that stimulate colon 5‐HT biosynthesis from colonic enterochromaffin cells .…”
Section: Discussionmentioning
confidence: 99%
“…Clinical investigations suggested that intestinal microflora is closely related to the health of an individual (Sekirov, 2010). Many diseases or conditions associated with suboptimal health are proved to be related with intestinal microbiota, such as depression (Cheung et al, 2019), chronic constipation (Ohkusa, Koido, Nishikawa, & Sato, 2019), and nonalcoholic liver disease (Ding et al, 2019). Similarly, numerous investigations have been devoted to elucidating the role of intestinal microflora in mammals (Pasinetti et al, 2018;Roselli et al, 2017) and fishes (Gómez & José Luis, 2010;Zhou, Ringø, Olsen, & Song, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Traditional cultivation‐dependent technique for microorganism research was limited by numerous microorganisms that cannot be cultured now, and cannot reflect the alteration of microbiota community. However, the advent of amplicon sequencing offered us an insight of the entire community structure and those uncultured microorganisms (B. Chen et al, ; Cheung et al, ; Shao et al, ). More and more nonegligible roles of intestinal microflora were revealed by sequencing technology.…”
Section: Discussionmentioning
confidence: 99%
“…However, the advent of amplicon sequencing offered us an insight of the entire community structure and those uncultured microorganisms (B. Chen et al, 2016;Cheung et al, 2019;Shao et al, 2017). More and more nonegligible roles of intestinal microflora were revealed by sequencing technology.…”
Section: Discussionmentioning
confidence: 99%